Extracellular vesicles as nature's nano carriers in cancer therapy: Insights toward preclinical studies and clinical applications - Xiaotong Wu; Yuhua Meng; Zhimeng Yao; Xiaona Lin; Mengyuan Hu; Songwang Cai; Shegan Gao; Hao Zhang (Pharmacological Research)
Extracellular vesicles (EVs), which are secreted by various cell types, hold significant potential for cancer therapy. However, there are several challenges and difficulties that limit their application in clinical settings. This review, which integrates the work of our team and recent advancements in this research field, discusses EV-based cancer treatment strategies to guide their clinical application. The following treatment strategies are discussed: 1) leveraging the inherent properties of EVs for the development of cancer treatments; 2) modifying EVs using EV engineering methods to improve drug loading and delivery; 3) targeting key molecules in tumor-derived EV (TDE) synthesis to inhibit their production; and 4) clearing TDEs from the tumor microenvironment. Additionally, on the basis of research into EV-based vaccines and bispecific antibodies, this review elaborates on strategies to enhance antitumor immunity via EVs and discusses engineering modifications that can improve EV targeting ability and stability and the research progress of Artificial intelligence (AI) technology in targeted delivery of EV drugs. Although there are limited strategies for enhancing EV targeting abilities, this review provides an in-depth discussion of prior studies. Finally, this review summarizes the clinical progress on the use of EVs in cancer therapy and highlights challenges that need to be addressed.